2018
DOI: 10.1186/s12882-018-1016-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hemodialysis on mortality risk and cause of death in Staphylococcus aureus endocarditis

Abstract: BackgroundThe risk of infective endocarditis (IE) is markedly increased in patients receiving chronic hemodialysis compared with the general population, but outcome data are sparse. The present study investigated causes and risk factors of mortality in a hemodialysis-treated end-stage kidney disease- (ESKD) and a non-ESKD population with staphylococcus (S.) aureus endocarditis.MethodsHemodialysis-treated ESKD patients with S. aureus endocarditis were identified from Danish National Registries and Non-ESKD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
1
8
1
Order By: Relevance
“…Complicated SAB represented 67.6% of the cohort, with the median age of the cohort 68.5 years (IQR:29.0). Age was significantly associated with complications and this is also reflected in other studies [ 5 , 32 , 36 , 43 ].…”
Section: Discussionsupporting
confidence: 78%
“…Complicated SAB represented 67.6% of the cohort, with the median age of the cohort 68.5 years (IQR:29.0). Age was significantly associated with complications and this is also reflected in other studies [ 5 , 32 , 36 , 43 ].…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies conducted in oncology, hemodialysis and ICU patients with a S. aureus CLABSI all found higher mortality rates (19–24% [ 16 , 36 ], 10–19% [ 37 , 38 ] and 18–53% [ 39 ], respectively). Our data on mortality and survival probabilities are, however, difficult to compare with the previous literature, because reported time periods and used mortality definitions differ highly among studies [ 11 , 12 , 14 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. For example, Ghanem et al [ 36 ] reported all-cause mortality at 3 months, while Blot et al [ 39 ] reported a 30-day all-cause mortality, and Fowler et al [ 14 , 43 ] frequently report on SAB attributable mortality.…”
Section: Discussionmentioning
confidence: 95%
“…For example, Ghanem et al [ 36 ] reported all-cause mortality at 3 months, while Blot et al [ 39 ] reported a 30-day all-cause mortality, and Fowler et al [ 14 , 43 ] frequently report on SAB attributable mortality. As said, chosen time periods to determine mortality rates differ widely as well: calculation may be based on days counted between death date and either date of positive blood culture or either date of discharge or even date of treatment discontinuation [ 11 , 12 , 14 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 Patients receiving dialysis are predisposed to infections due to several factors such as old age, diabetes, accumulation of uraemic toxins, and an impaired immune system. 10 Additionally, the use of temporary or permanent catheters as vascular access and the frequent skin perforation in the use of AV fistulae are acknowledged as the most likely port of entrance for bacteraemia and sepsis. 11 Amoxicillin/clavulanic acid and clindamycin are frequently used antibiotics in patients in need of chronic HD, mainly to treat respiratory infections and wound infections.…”
Section: Discussionmentioning
confidence: 99%